PAI SUPERVISOR ACADEMIC SUPERVISION MANAGEMENT IN INCREASING THE COMPETENCE OF MILLENIAL PAI TEACHERS - Romdhoni, Mochamad Rifki; Rahman, Lawal (TARBAWY: Indonesian Journal of Islamic Education, 2022)
Abstract While the majority of research on academic supervision by supervisors is not related to current conditions, this research is focused on the millennial era. This study aims to describe the academic supervision carried out by Supervisors for Islamic Religious Education (IRE) Teachers at SMA and SMK Bandung City in pedagogic, professional, social, personality, spiritual and leadership competencies. This study chose a qualitative descriptive design approach to three IRE supervisors and 34 IRE teachers. The results of the study illustrate that planning, organizing and coordinating, implementing, evaluating, and supervising follow-up have achieved the target of increasing a number of IRE teacher competencies. The millennial era has become a pressure point for IRE supervisors by supervising and fostering teachers in using information and technology facilities. To balance IT skills, IRE supervisors also emphasize the importance of building the spiritual character of teachers, so that they are professionally and spiritually responsible.Abstrak Sementara mayoritas penelitian tentang supervisi akademik oleh pengawas tidak dikaitkan dengan kondisi zaman, maka penelitian ini difokuskan dalam era milenial. Penelitian ini bertujuan mendeskripsikan supervisi akademik yang dilakukan Pengawas terhadap Guru Pendidikan Agama Islam (PAI) SMA dan SMK Kota Bandung pada kompetensi pedagogik, profesional, sosisal, kepribadian, spiritual dan leadership. Penelitian ini memilih pendekatan kualitatif desain deskriptif terhadap tiga Pengawas PAI dan 34 Guru PAI. Hasil penelitian menggambarkan perencanaan, pengorganisasian dan koordinasi, pelaksanaan, evaluasi, dan tindak lanjut supervisi telah mencapai target peningkatan sejumlah kompetensi Guru PAI. Era milenial menjadi titik tekan Pengawas PAI dengan mengawasi serta membina Guru dalam menggunakan fasilitas informasi dan teknologi. Untuk menyeimbangkan kemampuan IT, Pengawas PAI juga menekankan pentingnya membangun karakter spiritual Guru, sehingga mereka bertanggungjawab secara profesional dan spiritual.